If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20 + -1(x + 9) = 6x + -3 Reorder the terms: 20 + -1(9 + x) = 6x + -3 20 + (9 * -1 + x * -1) = 6x + -3 20 + (-9 + -1x) = 6x + -3 Combine like terms: 20 + -9 = 11 11 + -1x = 6x + -3 Reorder the terms: 11 + -1x = -3 + 6x Solving 11 + -1x = -3 + 6x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6x' to each side of the equation. 11 + -1x + -6x = -3 + 6x + -6x Combine like terms: -1x + -6x = -7x 11 + -7x = -3 + 6x + -6x Combine like terms: 6x + -6x = 0 11 + -7x = -3 + 0 11 + -7x = -3 Add '-11' to each side of the equation. 11 + -11 + -7x = -3 + -11 Combine like terms: 11 + -11 = 0 0 + -7x = -3 + -11 -7x = -3 + -11 Combine like terms: -3 + -11 = -14 -7x = -14 Divide each side by '-7'. x = 2 Simplifying x = 2
| 5s+27=172 | | x^2-14x-53=0 | | -3/5*-1/9 | | 2-n=-1 | | t+12=12 | | 25.56+x=25.72 | | 14-3f=2 | | x-10=3x-12 | | -2-n=0 | | 90=-2(3-6k) | | 3r+19=4-2r | | logx=0.32 | | 2(x+6)=3(x+7) | | x+1=12x-1 | | 3/5*(-1/6) | | 3r/10=6 | | -2.73+x=-.3 | | q/-5=18 | | 2log(3x+5)=4 | | -19.5=9.5x-5.5x | | 12(x+1)=-3 | | 22=x-7.8 | | 14-5x=-52 | | 121=4x+7 | | 4(x-5)=2(x+2) | | x+15+75=x | | (x-lnx*2x)/x^4 | | -3x+8x=10 | | 2n-3/7=1n-2/5 | | x+15=x+75 | | -6x+8=-3x-10 | | 6x-3x=-15 |